Trans-scleral Effect of Mitomycin-C on Ciliary Body Epithelium - Mahar, P.S. (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the toxic effect of intraoperative adjunctive topical Mitomycin C (MMC) on ciliary body epithelium resulting in decrease in intraocular pressure (IOP). Material and Methods: An interventional case series of 120 patients (120 eyes) with pterygium treated from 2005 to 2010. All patients underwent pterygium excision with intraoperative MMC, (0.2 mg/mL) administered for 3 minutes. The toxic effect of MMC on ciliary body was determined through changes in the IOP. Any change in IOP of greater than 5 mm Hg was considered significant. The IOP was recorded on day 1, day 7, at 1 month and at 3 months. The data were analyzed using proportion, group means, standard deviations and student t test. Results: There was no significant decline in IOP throughout the follow-up period (p = 0.44). At 3 months postoperatively, 105 eyes (87.5%) had no changes in IOP of >5 mm Hg. The mean IOP changed from a preoperative level of 14.85 mm Hg to 14.44 mm Hg at 3 months follow up signifying no change statistically. Conclusions: Our results showed that use of MMC as an adjunctive treatment in pterygium excision has no effect on intraocular pressure and do not support the trans-scleral toxic effect of MMC on the ciliary body epithelium as an intraocular pressure lowering mechanism.